2017
DOI: 10.1016/j.pedneo.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Early provision of oropharyngeal colostrum leads to sustained breast milk feedings in preterm infants

Abstract: OC application for VLBW infants is safe and practical in a neonatal intensive care unit setting and is associated with increased rates of breast milk feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 34 publications
(39 reference statements)
0
34
0
9
Order By: Relevance
“…The practice of providing early application of oropharyngeal colostrum has been proposed as a protective strategy prior to introduction to enteral breast milk feeds. A non‐randomised controlled cohort study by Snyder et al . found that the early provision of oropharyngeal colostrum through enteral feeds was significantly associated with continued provision of breast milk feeds at 6 weeks of age ( P = 0.03) and through discharge ( P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The practice of providing early application of oropharyngeal colostrum has been proposed as a protective strategy prior to introduction to enteral breast milk feeds. A non‐randomised controlled cohort study by Snyder et al . found that the early provision of oropharyngeal colostrum through enteral feeds was significantly associated with continued provision of breast milk feeds at 6 weeks of age ( P = 0.03) and through discharge ( P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Premature infants often suffer from stomach retention, abdominal distension and vomiting due to immature digestive system [19]. Gastric retention, also known as gastric emptying delay, the results showed that the residual gastric fluid extracted from the stomach before feeding was more than 50% of the previous feeding.…”
Section: Colostrums Oral Intervention Can Accelerate the Process Of Nmentioning
confidence: 99%
“…Mothers held neonatologists’ breastfeeding recommendations in high regard, even when specifics of why and how milk expression and at-breast feeds might proceed were not discussed (“ I’m just kind of doing what nurses and doctors tell me to do”). Notably, no women had attempted human milk oral care or were aware of the potential benefits of this practice prior to initiation of oral feeds ( 15 , 16 ).…”
Section: Resultsmentioning
confidence: 99%